Triple-Probiotic-Fermented Goji (Lycium barbarum L.) Ameliorates Metabolic Disorders Associated with Hyperuricemia in Mice - Lu Ren; Yuechan Li; Shiting Liu; Xiaoke Jia; Hongpeng He; Feiliang Zhong; Fuping Lu; Xuegang Luo (Microorganisms, 2025)
Hyperuricemia (HUA) is a metabolic disorder characterized by excessive uric acid (UA) production and impaired excretion. Goji, as a representative medicinal food, holds significant research and development value, while probiotic fermentation technology is finding increasingly widespread applications in the functional food sector. This study developed a novel goji fermented with three probiotic strains (Lactoplantibacillus plantarum CGMCC8198, Lactococcus lactis LTJ28, and Lactocaseibacillus casei YR2-2) and investigated its anti-HUA effects. Optimal fermentation conditions (7.913 material–liquid ratio, 3.92% inoculation, 7.49 h at 37 °C with 1:1:2 strain ratio) yielded a beverage with enhanced flavor profiles (19 aroma compounds) and high viable counts. In HUA cell models, the 15% fermented goji juice significantly reduced UA levels by 56% (p < 0.01). In potassium oxonate-induced HUA mice, the beverage effectively lowered serum UA, xanthine oxidase activity, and renal function markers (blood urea nitrogen and creatinine, p < 0.0001) while improving hepatic parameters (alanine aminotransferase, aspartate Aminotransferase). The goji-fermented juice significantly reduced the expression of renal UA transporters GLUT9 and URAT1 (p < 0.0001) while improving gut microbiota composition, as evidenced by increased beneficial SCFAs (acetic acid, butyric acid, p < 0.0001) and elevated Lactobacillus abundance 2.14-fold. Our findings demonstrate that this triple-probiotic-fermented goji beverage represents an effective dietary strategy for HUA management by simultaneously inhibiting UA production, enhancing excretion, and restoring gut microbiota homeostasis, providing a scientific basis for developing probiotic-based functional foods against HUA.